Effects of two post-grazing heights on morphogenic and structural characteristics of guinea grass under rotational grazing - Da Cunha B.A.L. (2010)
A rotational grazing experiment was carried out to determine the effects of post-grazing height on morphogenic characteristics of guinea grass (Panicum maximum) cv. Mombaca between October 2004 and June 2005. The grass was subjected to 2 severities of rotational grazing, represented by post-grazing stubble heights of 30 and 50 cm, and animals were reintroduced when pastures intercepted 95% of incident light. Swards managed with 30 cm post-grazing stubble height had smaller leaf elongation rate (LER) and final leaf length (FLL) and greater tiller population density (TPD), tiller appearance rate (TAR) and tiller mortality rate (TMR) than those grazed to 50 cm. During the second grazing cycle, stem elongation rate (SER) was lower in paddocks grazed to 30 cm stubble height. Grazing cycle had significant effects on plant morphology. Leaf appearance rate (LAR), LER and TAR peaked in the second grazing cycle, while SER, TPD and TMR peaked in cycles 3 and 4. The more intense grazing management (30 cm stubble) resulted in higher levels of tiller renewal and tiller turnover and lower stem elongation. How these changes relate to pasture yields and animal performance is yet to be determined.